2010
DOI: 10.1007/s12018-010-9071-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of Osteoporosis

Abstract: Pharmacogenomics and pharmacogenetics are emerging interdisciplinary areas recently defined, respectively as ''the investigation of variations of DNA and RNA characteristics as related to drug response'', and the study of ''the influence of variations in DNA sequence on drug efficacy and toxicity''. A major challenge of future genetic studies in complex disorders such as osteoporosis is the development of specific genetic tests to identify responders from non-responders as well as to identify patients at highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 138 publications
1
6
0
Order By: Relevance
“…First evidence for an interaction between calcium intake and BsmI VDR polymorphism came from a study by Ferrari et al 19 in a sample of elderly patients receiving calcium and calcitriol supplements, among whom BMD loss was higher in the lumbar spine of the homozygotes for the B allele. Similar results, indicative of the genetreatment interaction, were found in other studies (for a review see Gennari 21 ) were the BB genotype associated with higher response to calcium administration, reduced efficiency of calcium absorption and low response of BMD. Furthermore, a large-scale study 15 reported evidence of weak interactions between calcium intake, VDR variants and BMD as well as with rates of bone loss in a way that favored the bb homozygotes in the lowest calcium intake quartile.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…First evidence for an interaction between calcium intake and BsmI VDR polymorphism came from a study by Ferrari et al 19 in a sample of elderly patients receiving calcium and calcitriol supplements, among whom BMD loss was higher in the lumbar spine of the homozygotes for the B allele. Similar results, indicative of the genetreatment interaction, were found in other studies (for a review see Gennari 21 ) were the BB genotype associated with higher response to calcium administration, reduced efficiency of calcium absorption and low response of BMD. Furthermore, a large-scale study 15 reported evidence of weak interactions between calcium intake, VDR variants and BMD as well as with rates of bone loss in a way that favored the bb homozygotes in the lowest calcium intake quartile.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, animal studies 32 suggested that teriparatide shifts stem cells towards the osteoblasts linage. However, teriparatide's effect has not been evaluated in pharmacogenomic studies yet 21 . The results of the present pilot study suggest that in contrast to alendronate, no interaction seems to exist between VDR BsmI polymorphism and teriparatide treatment.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…They included the vitamin D receptor, estrogen receptors, collagen and lipoprotein receptor-related protein (a Wnt coreceptor), but the results have not been adequately replicated. 16,23,24 In this study, we analyzed the relationship of several polymorphisms of the gene encoding the FDPS enzyme, a major target of aminobisphosphonates, with BMD and drug response in postmenopausal women. We only found a quantitatively small and not significant trend for association of one of the SNPs studied with baseline hip BMD.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Similarly, little is known about the pharmacogenomics of osteoporosis, and specifically about the possible influence of genetic factors on the therapeutic effects of antiosteoporotic drugs. 16 The aim of this study was to analyze the influence of FDPS polymorphisms on BMD and the response to antiresorbing drugs.…”
Section: Introductionmentioning
confidence: 99%